2022
DOI: 10.1038/s41420-022-00846-4
|View full text |Cite
|
Sign up to set email alerts
|

ECM1 modified HF-MSCs targeting HSC attenuate liver cirrhosis by inhibiting the TGF-β/Smad signaling pathway

Abstract: Hair follicle-derived mesenchymal stem cells (HF-MSCs) show considerable therapeutic potential for liver cirrhosis (LC). To improve the effectiveness of naïve HF-MSC treatments on LC, we used bioinformatic tools to identify an exogenous gene targeting HSCs among the differentially expressed genes (DEGs) in LC to modify HF-MSCs. Extracellular matrix protein 1 (ECM1) was identified as a DEG that was significantly downregulated in the cirrhotic liver. Then, ECM1-overexpressing HF-MSCs (ECM1-HF-MSCs) were transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…ECM1-modified HFMSCs blocked the activation of HSCs via inhibiting the TGF-β/Smad signaling pathway in vitro and in vivo. Besides, ECM1-modified HFMSCs migrated to the injury sites of the liver and expressed hepatocytespecific surface markers, thus ameliorating liver fibrosis and promoting liver repair and enhancing liver function [133]. All data suggest that genetic modification of MSCs is beneficial in enhancing therapeutic effects for liver fibrosis.…”
Section: Efforts To Improve the Therapeutic Performance Of Mscsmentioning
confidence: 84%
See 2 more Smart Citations
“…ECM1-modified HFMSCs blocked the activation of HSCs via inhibiting the TGF-β/Smad signaling pathway in vitro and in vivo. Besides, ECM1-modified HFMSCs migrated to the injury sites of the liver and expressed hepatocytespecific surface markers, thus ameliorating liver fibrosis and promoting liver repair and enhancing liver function [133]. All data suggest that genetic modification of MSCs is beneficial in enhancing therapeutic effects for liver fibrosis.…”
Section: Efforts To Improve the Therapeutic Performance Of Mscsmentioning
confidence: 84%
“…Viral vector-mediated 9 Stem Cells International gene modification provides a potential new approach for remodeling MSCs, including lentiviruses, adenoviruses, and retroviruses, which enables MSCs to express a variety of exogenous genes with high expression and hardly affects the biological characteristics of MSCs [124]. Genes transfected into MSCs are classified as MMPs [125], microRNAs [87,126], trophical factors [63,[127][128][129][130], transcription factors [131,132], and ECM protein [133].…”
Section: Efforts To Improve the Therapeutic Performance Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair follicles, as natural reservoirs of MSCs, are recognized as having advantages over other sources of MSCs [13]. In previous studies, HFMSCs have been suggested to be effective in the treatment of hair loss [30], pancreatitis [44], and liver cirrhosis [45] due to their anti-inflammatory properties and their ability to differentiate into parenchymal cells. However, there have been few studies on HFMSCs in the context of UC.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous cell types that can be used in the treatment of liver fibrosis and cirrhosis, such as mesenchymal stem cells (MSCs), umbilical cord mesenchymal stem cells (UCMSCs), bone marrow mesenchymal stem cells (BMMSCs), liver-derived mesenchymal stem cells (LDMSCs), and so on. Stem cell-based therapies are less intrusive for patients than surgical procedures and have a minimal risk of immunological rejection when compared to traditional therapeutic approaches [ 64 ]. In a CCl4-induced liver cirrhosis mouse model, hair follicle mesenchymal stem cells (HF-MSCs) with ECM1 modification exhibited a better effect on promoting injured liver repair and improving liver function, which may provide a relevant theoretical basis for the application of ECM1-HF-MSCs in liver cirrhosis treatment [ 65 ].…”
Section: Current Interventions In Liver Fibrosis Managementmentioning
confidence: 99%